PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTsN 2 BANDA ACEH KELAS VIII MELALUI MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) - Septirahmi, Resiana; M. Yacoeb; Susanti (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2024)
Mathematical communication skills have an important role in learning mathematics. However, the reality in the field shows that students' mathematical communication skills are still low. So we need a learning model that can improve students' mathematical communication skills. Therefore, the CORE learning model was chosen. This study aims (1) to determine the learning process using the CORE model which can improve mathematical communication skills; (2) to determine the increase in mathematical communication skills taught using the CORE model. The subjects in this study were students of class VIII-4 at MTsN 2 Banda Aceh. The indicators that are measured are written text, drawing and mathematical expression. Data collection was used by using a mathematical communication ability test sheet. Furthermore, the data were analyzed qualitatively by describing the facts or facts in accordance with the data obtained and also used the N-Gain test. The results of this study indicate that (1) In the written text indicator students can write a concept and accompanied it with appropriate explanations, on the drawing indicator students can present images in mathematical ideas appropriately, and on mathematical expression indicators students can write information from a problem inward. mathematical model; (2) N-Gain test with an average of 0.51 in the